Case studies in entrepreneurship - Reed, Marlene M.; Brunson, Rochelle R. (Edward Elgar Publishing, 2021)
"Most entrepreneurship and small business textbooks contain few, if any, cases that an instructor can use with students and illustrate important theories or topics from the course. This book contains cutting-edge case studies that illustrate key problems confronting contemporary entrepreneurs. Set in familiar business environments, this original set of cases provides useful insights into the experiences of real-world entrepreneurs for classroom environments. Key features include: Innovative and exciting cases that present common business scenarios, offering practical perspectives for up-and-coming entrepreneurs A theory-based online Instructor's Manual, featuring topic summaries, learning objectives, teaching suggestions and key questions to aid classroom discussion Exceptional coverage of critical entrepreneurship issues, including opportunity recognition, funding a new business, sustaining ventures, social entrepreneurship and challenges faced by collegiate entrepreneurs. An ideal companion for instructors and students, this book is essential reading for MBA courses in entrepreneurship, non-profit management and social entrepreneurship, as well as undergraduate and postgraduate courses in business and management that specialize in entrepreneurship"--